Alexander the Great - Gunther, John, 1901-1970.; Barnett, Isa (New York, Random House, 1953)
A life of the warrior who, as a prince, tamed the powerful horse Bucephalus and, during his short reign as king, built an empire that covered almost all of the then-known world, including Greece, India, Egypt, and Persia.
Keywords: Alexander, -- the Great, -- 356 B.C.-323 B.C. -- Juvenile literature; Alexander, -- the Great, -- 356 B.C.-323 B.C.; Generals -- Greece -- Biography -- Juvenile literature; Greece -- History -- Macedonian expansion, 359-323 B.C. -- Juvenile literature; Greece -- Kings and rulers -- Biography -- Juvenile literature